2016
DOI: 10.5489/cuaj.3780
|View full text |Cite
|
Sign up to set email alerts
|

The Western snip, stitch, and tug hydrocelectomy: How I do it

Abstract: Introduction: Adult idiopathic hydrocele is a common benign disorder that merits surgical correction when symptomatic. The most popular techniques for repair are plication (Lord's procedure) or excision and eversion of the tunica vaginalis (Jaboulay procedure). Established complications from these traditional repairs include hematoma, recurrence, and infection. These procedures are performed through a scrotal incision. We describe a novel technique of hydrocele repair with gubernaculum preservation through a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In seven (15.2%) cases, the authors simply reported that the testes were fixed bilaterally. 21,24,37 In another seven cases it was described as fixation of the testes to the dartos (n = 5, 10.9%), 35,36 scrotal wall (n = 1, 2.2%) 18 and tunica vaginalis (n = 1, 2.2%), 27 in four cases it was described as fixation of the tunica albuginea to the scrotal wall (n = 2, 4.4%), 17,31 the septum (n = 1, 2.2%) 26 and the tunica vaginalis (n = 1, 2.2%), 37 while in eight (17.4%) cases, 14,23,27 Jaboulay's technique (external eversion of the tunica vaginalis with suturing of the free edges posterior to the spermatic cord) 38 was used.…”
mentioning
confidence: 99%
“…In seven (15.2%) cases, the authors simply reported that the testes were fixed bilaterally. 21,24,37 In another seven cases it was described as fixation of the testes to the dartos (n = 5, 10.9%), 35,36 scrotal wall (n = 1, 2.2%) 18 and tunica vaginalis (n = 1, 2.2%), 27 in four cases it was described as fixation of the tunica albuginea to the scrotal wall (n = 2, 4.4%), 17,31 the septum (n = 1, 2.2%) 26 and the tunica vaginalis (n = 1, 2.2%), 37 while in eight (17.4%) cases, 14,23,27 Jaboulay's technique (external eversion of the tunica vaginalis with suturing of the free edges posterior to the spermatic cord) 38 was used.…”
mentioning
confidence: 99%
“…Procedures were successfully completed for all 42 patients. Although some researchers 12 have performed hydrocelectomy in an outpatient setting, we recommended 3 days of hospitalization in case of any unexpected AEs.…”
Section: Resultsmentioning
confidence: 99%
“…We identified favorable early outcomes in men undergoing our MIMFeT for treatment of symptomatic hydroceles. 6,12,[19][20][21] This procedure can be performed safely and effectively in the office under local anesthesia. In the current era of ever-increasing medical costs, the ability to perform this and other urologic procedures under local anesthesia has important and meaningful implications for our patients and the healthcare system as a whole.…”
Section: Discussionmentioning
confidence: 99%